2019
DOI: 10.33679/rmi.v1i1.2153
|View full text |Cite
|
Sign up to set email alerts
|

El “nuevo racismo” desde la lente de la “migración silenciosa”: la adopción interracial en España

Abstract: The increase in international adoptions of minors (quiet migration) all over Spain has coincided in time with the rise of immigration. The links between these two phenomena give rise to a hybrid line of research focused on the racial experiences shared by both the adopted population and the immigrant population. A comparative analysis of data coming from three public opinion research sources reveals: (a) the presence of “racism without race” within Spanish society, even though phenotypic differences play a det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
4
0
2
Order By: Relevance
“…The existence of racism in Spain, especially towards African or African-descended persons, is a real fact that often captures headlines on the pages of the most recognized digital newspapers (García, 2017; Sociedad Civil Africana y Afrodescendiente, 2016; Es Racismo, 2018). What stands out along with the condemnation is a call for recognition of a renascent cultural identity (Rodríguez & Llanas, 2019; Saíz, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of racism in Spain, especially towards African or African-descended persons, is a real fact that often captures headlines on the pages of the most recognized digital newspapers (García, 2017; Sociedad Civil Africana y Afrodescendiente, 2016; Es Racismo, 2018). What stands out along with the condemnation is a call for recognition of a renascent cultural identity (Rodríguez & Llanas, 2019; Saíz, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Tüm bu konvansiyonel savaşların yanı sıra siber saldırılar, kimyasal ve biyolojik tehditler gibi durumları da içinde barındıran hibrit savaşlar da yaşanmaktadır. Ayrıca düşman grubu egale etmek için yurtiçi yasadışı çatışma üretme olarak tanımlanabilecek 46 terörizm, hibrit ve mobilize teknolojilerle bütünleşerek yeni terörizme evrilmiştir 47 Bu gelişmeler de çeşitli yeni güvenlik problemlerini beraberinde getirmiştir.…”
Section: Yakın çAğ'da Savunma Ve Sığınma Olgusunun Mekâna Yansımasıunclassified
“…In-country and inter-country adoption in India [2] The article examines the social views towards interracial adoptions and its critical impacts on children development. It is identified that racial discrimination leads to bullying in interracial adoption which negatively impacts the mental health of children as well as their upbringing [3]. A brief discussion regarding interracial adoption and its effect on Indian society is presented in this article.…”
Section: Figurementioning
confidence: 99%
“…Every race has a different culture and interracial adoption helps people to evolve with different cultures of the world and expand their knowledge. The previous generation never accepted interracial adoption but the people in the 21st generation are proudly and profoundly accepting the process which is changing the old norms of society and the people of this modern age are making their own rules and norms for society [9]. This adoption process inspires people to learn about new traditions and helps them to adopt new cultural ideas and gather more new experiences.…”
Section: Pros and Cons Of Interracial Adoptionmentioning
confidence: 99%
See 1 more Smart Citation